The influence of wushu on the indicators of the respiratory system of athletes 17-18 years old - Chernenko, O.; Serdyuk, D.; Chernenko, A.; Черненко, Олена Євгенівна (My University, 2021)
The problem of achieving high results in wushu sports requires the improvement of methods and tools of the training process, which is associated with a comprehensive study of the abilities and functional capabilities of athletes. It is established that at the stage of sports improvement of wushu athletes the main emphasis in training of athletes should be put on increasing the level of functional possibilities of an organism of athletes. The obtained results indicate a positive effect of training on the functional state of the respiratory system of athletes. The largest relative increase in the indicators of the respiratory system was found in the Stange sample (33.4%). Taking into account all other indicators there was a significant relative increase, for more than 10%.
Keywords: functional state; respiratory system; wushu; athletes; preparatory period